2007
DOI: 10.1038/sj.hdy.6800935
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and fine-scale spatial-genetic structure in British wild cherry (Prunus avium L.)

Abstract: Insights into the within-population spatial-genetic structure (SGS) of forest tree species, where little is known regarding seed and pollen dispersal patterns, enhance understanding of their ecology and provide information of value in conservation and breeding. This study utilised 13 polymorphic simple sequence repeat loci to investigate the impact of asexual recruitment, management regime and tree size on the development of SGS in wild cherry (Prunus avium L). Only 246 genotypes were identified in the 551 tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
34
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 32 publications
7
34
3
Order By: Relevance
“…Less than 10% of compatible pollen donor genets grew within this distance and as such it seems that insect pollinator behaviour must be a key determinant of paternal success in wild cherry. This finding underpins the strong SGS observed earlier at this site in distance classes up to 120 m (Vaughan et al, 2007a) as a prevalence of short-distance pollination events would increase the kinship coefficient of individuals at this scale. However, mother trees differed greatly in the proportion of seed they produced that was pollinated by close neighbours and our analysis indicated that tree size and membership of a clonal genet were primary variables in determining pollination success.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…Less than 10% of compatible pollen donor genets grew within this distance and as such it seems that insect pollinator behaviour must be a key determinant of paternal success in wild cherry. This finding underpins the strong SGS observed earlier at this site in distance classes up to 120 m (Vaughan et al, 2007a) as a prevalence of short-distance pollination events would increase the kinship coefficient of individuals at this scale. However, mother trees differed greatly in the proportion of seed they produced that was pollinated by close neighbours and our analysis indicated that tree size and membership of a clonal genet were primary variables in determining pollination success.…”
Section: Discussionsupporting
confidence: 48%
“…Indeed, in other tree species, it has been shown that the spatial arrangement and the local density of the adult trees shape pollen dispersal patterns and a clumped arrangement has been found to favour shorter intermate distances compared with more regular distributions (Handel, 1983;Garcia et al, 2005). Significantly, cherry exhibits a clumped distribution interspersed within mixed woodland (Vaughan et al, 2007a). This is likely to cause the number and distribution of pollen donors around individual mother trees to be highly variable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that two individuals carrying the same genotype at the S-locus will not be compatible. Pollen is dispersed by bees, and seeds by gravity and birds, resulting in low dispersal distances (Granger, 2004;Schueler, 2005;Stoeckel, 2006) and consequently in significant spatial genetic structure (Vaughan et al, 2007b;. Vegetative propagation through rootsuckering commonly occurs and, as a consequence, clusters of clonal individuals can be identified within the stands (Ducci and Santi, 1997;Schueler, 2005;Schueler et al, 2006;Vaughan et al, 2007a;.…”
Section: Introductionmentioning
confidence: 99%
“…When multiloci genotype repeats are removed, the single "genet" can be reckoned to derive from sexual reproduction (SMITH et al, 1993;VAUGHAN et al, 2007;WALSER et al, 2004), and its genetic variation can reflect the sexual reproductive status in species. Thus, by comparing with the other similar lifehistory species, the "genet-level" genetic diversity (H E = 0.582) and differentiation (F ST = 0.172) of C. chinensis are comparable to or lower than those in other studies ("data from SSR", Table 3).…”
Section: Populations Suffer From Bottleneckmentioning
confidence: 99%